2017
DOI: 10.1097/ede.0000000000000670
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Virus Interference in a Test-negative Study of Influenza Vaccine Effectiveness

Abstract: Background The observational test-negative study design is used to estimate vaccine effectiveness against influenza virus infection. An important assumption of the test-negative design is that vaccination does not affect the risk of infection with another virus. If such virus interference occurred, detection of other respiratory viruses would be more common among influenza vaccine recipients and vaccine effectiveness estimates could differ. We evaluated the potential for virus interference using data from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 44 publications
1
30
1
Order By: Relevance
“…Virus interference associated with influenza vaccination has been previously investigated [7][8][9][10][11][12]. However, this study was the first virus interference study conducted among highly vaccinated DoD personnel.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Virus interference associated with influenza vaccination has been previously investigated [7][8][9][10][11][12]. However, this study was the first virus interference study conducted among highly vaccinated DoD personnel.…”
Section: Resultsmentioning
confidence: 97%
“…While influenza vaccination offers protection against influenza, natural influenza infection may reduce the risk of non-influenza respiratory viruses by providing temporary, non-specific immunity against these viruses [7,8]. On the other hand, recently published studies have described the phenomenon of vaccine-associated virus interference; that is, vaccinated individuals may be at increased risk for other respiratory viruses because they do not receive the non-specific immunity associated with natural infection [7][8][9][10]. There has been limited evidence that the influenza vaccine may actually be associated with the virus interference process [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…The studies covered the 2003/2004 to 2013/2014 influenza seasons and 7 countries, including Australia (4 studies ( 24 , 27 , 28 , 31 )), the United States (3 studies ( 26 , 32 , 34 )), Japan (1 study ( 33 )), China (Hong Kong; 1 study ( 25 )), Portugal (1 study ( 29 )), New Zealand (1 study ( 30 )), and the Netherlands (1 study ( 35 )) (Table 1 ). Five studies reported estimates for a single year ( 27 , 29 – 31 , 33 ), while others reported estimates across multiple years ( 24 – 26 , 28 , 32 , 34 , 35 ). Among 7 studies reporting pooled estimates across more than 1 year/season, 3 studies also provided season-specific estimates ( 28 , 34 , 35 ).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies reported estimates for a single year ( 27 , 29 – 31 , 33 ), while others reported estimates across multiple years ( 24 – 26 , 28 , 32 , 34 , 35 ). Among 7 studies reporting pooled estimates across more than 1 year/season, 3 studies also provided season-specific estimates ( 28 , 34 , 35 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation